Biological treatment of coke making wastewater. - Raper, Eleanor (Cranfield University, 2017)
Production of coke for steel manufacturing produces a wastewater containing total nitrogen (TN) (up to 600 mg/L) alongside toxic compounds phenol (60 - 400 mg/L), thiocyanate (SCN-) (100 - 400 mg/L), polycyclic aromatic hydrocarbons (PAHs) (Ʃ6PAHs:179±35 µg/L) and trace metals. Emission limits introduced by the Industrial Emissions Directive (IED) in 2016 require treated coke effluent to contain <50 mg/L TN, <4 mg/L SCN-, <0.5 mg/L phenol and <50 µg/L Ʃ6PAHs which cannot be consistently met by the conventional activated sludge process (ASP). Treatment process modifications were investigated to ensure compliance. Activated carbon addition to the ASP (400 mg/L) increased Ʃ6PAHs removal by 20% enabling emission compliance whilst increasing nickel, chromium and cadmium removal. The addition of 0.5 g/L of a commercial bioaugmentation product increased dissolved Ʃ6PAHs removal by 51%. Biostimulation (addition of micronutrients/alkalinity) enabled SCN-and phenol emission compliance. Survival of supplemented exogenous bacteria in a simulated river water discharge was investigated for the first time showing limited survivability. Thiocyanate degradation mechanisms were poorly understood but were important to ascertain, especially as SCN-degradation produces ammonia increasing TN loading. Control of influent ammonia and phenol concentration was important enabling SCN-degradation under anoxic and aerobic conditions. Deoxyribonucleic acid sequencing of the mixed culture identified a new species of Thiobacillus which had metabolic similarities to T. thioparus and T. denitrificans. Nitrification was limited (41%) confirming the importance of intrinsic alkalinity availability in the wastewater, however, sodium carbonate addition (300 mg/L as CaCO₃) increased efficiencies to 96%. An anoxic-aerobic ASP was investigated for TN removal enabling an effluent TN <50 mg/L when the soluble chemical oxygen demand (sCOD):TN ratio was maintained above 5.7. Acetic acid was identified as a suitable source of carbon addition to maintain this ratio. An anoxic-aerobic ASP combined with AC and bioaugmentation can ensure compliance with the IED.
Keywords: Coke wastewater; total nitrogen; thiocyanate; polycyclic aromatic hydrocarbons; phenol; trace metals; activated sludge process; activated carbon bioaugmentation; biostimulation